2016
DOI: 10.3390/ijms17071138
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Codon Usage Bias in Epichloë festucae

Abstract: Analysis of codon usage data has both practical and theoretical applications in understanding the basics of molecular biology. Differences in codon usage patterns among genes reflect variations in local base compositional biases and the intensity of natural selection. Recently, there have been several reports related to codon usage in fungi, but little is known about codon usage bias in Epichloë endophytes. The present study aimed to assess codon usage patterns and biases in 4870 sequences from Epichloë festuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…The ENC in grape bHLH genes ranged from 30.28 to 60.96, with an average of 53.25. Among the 94 grape bHLH genes, only one gene (VvbHLH091) exhibited high codon bias (ENC < 35), indicating that in general, grape bHLH genes reflect random codon usage without strong codon bias (Li et al, 2016 ). Codon usage bias could be affected by many stressors including mutation pressure and natural selection (Li, 1987 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ENC in grape bHLH genes ranged from 30.28 to 60.96, with an average of 53.25. Among the 94 grape bHLH genes, only one gene (VvbHLH091) exhibited high codon bias (ENC < 35), indicating that in general, grape bHLH genes reflect random codon usage without strong codon bias (Li et al, 2016 ). Codon usage bias could be affected by many stressors including mutation pressure and natural selection (Li, 1987 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on codon usage bias in E. festucae showed that both natural selection and mutation pressure played a role in forming codon usage bias in E. festucae , and that codon usage bias was influenced by CDS length (Li et al, 2016 ). There are 43 Epichloë species that have been reported to date, but it is not clear whether Epichloë species share similar codon usage bias.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that the GC3s was positively correlated with the GC12s (r ¼ 0.2239, p ¼ 0.3045). The slope of the neutrality plot was 0.03608, meaning that mutation pressure accounted for 3.608% of shaping the codon usage pattern and the influence from other factors was 96.392% [26].…”
Section: Neutrality Plot Analysismentioning
confidence: 99%